2017
DOI: 10.2528/pierm17052204
|View full text |Cite
|
Sign up to set email alerts
|

The Weakened Weibel Electromagnetic Instability of Ultra-Intense Mev Electron Beams in Multi-Layer Solid Structure

Abstract: Abstract-The Weibel instability of intense and collimated MeV fast electron beams in multi-layer structure is investigated. It is found that the electromagnetic instability of fast electron beams can be significantly suppressed by this structure. A strong magnetic field will be created at the interfaces between materials with different resistivities as these fast electrons are injected into this structure. It obstructs the transverse movement of the fast electrons and confines them to propagate along the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In this order, recent studies have shown that the resistive electromagnetic instabilities of fast electron beams can be significantly weakened by the multi‐layer structure where generating this magnetic field, which is related to the rotation of the gradient of the resistivity, pushes electrons towards the regions of higher resistivity. [ 11 ] However, it is found that other mechanisms tend to contribute to the self‐generated magnetic fields and transport process. [ 6,7,12 ] In this regard, in our previous work, we modelled the effects of plasma heating, pinching J×B, and Nernst (arising from the hot electrons flux) on the resistive filamentation modes in a magnetized anisotropic plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In this order, recent studies have shown that the resistive electromagnetic instabilities of fast electron beams can be significantly weakened by the multi‐layer structure where generating this magnetic field, which is related to the rotation of the gradient of the resistivity, pushes electrons towards the regions of higher resistivity. [ 11 ] However, it is found that other mechanisms tend to contribute to the self‐generated magnetic fields and transport process. [ 6,7,12 ] In this regard, in our previous work, we modelled the effects of plasma heating, pinching J×B, and Nernst (arising from the hot electrons flux) on the resistive filamentation modes in a magnetized anisotropic plasma.…”
Section: Introductionmentioning
confidence: 99%